(untitled) (Global Journal of Medical Research, 2017)
Mastitis is the most complex and costly disease of dairy cows occurring throughout the world including Ethiopia. Streptococcal mastitis is the commonest and economically important. However, mastitis caused by this species is not well investigated. A cross-sectional study was conducted from November 2016 to April 2017 to determinethe prevalence of mastitis, associated risk factor and also to isolate pathogenic streptococcus species from lactating dairy cows in and around Haramaya town, Eastern Ethiopia. A total of 384 milking cows and 1536 quarters were examined, out of which 189 and 677 were CMT positive at cow and quarter level respectively. The overall prevalence 49.2% (189/384) at cow level and 45.68% at quarter level were determined, respectively. Out this, 7.5%(29/384) were clinical mastitis and 41.7% (160/384) were subclinical and 6.8%clinical and 38.86% sub-clinical were found to be mastitis positive on CMT at cows and quarter level, respectively. Among total of 1536 quarters examined, 54 (3.5%) had blind teats. The age, lactation stage, parity and hygienic milking practice were found to have significant (p